Preservation of exopolymeric substances in estuarine sediments - Duteil, Thibault; Bourillot, Raphaël; Braissant, Olivier; Grégoire, Brian; Leloup, Maud; Portier, Eric; Brigaud, Benjamin; Féniès, Hugues; Svahn, Isabelle; Henry, Adrien; Yokoyama, Yusuke; Visscher, Pieter T. (Frontiers in Microbiology, 2022)
The surface of intertidal estuarine sediments is covered with diatom biofilms excreting exopolymeric substances (EPSs) through photosynthesis. These EPSs are highly reactive and increase sediment cohesiveness notably through organo-mineral interactions. In most sedimentary environments, EPSs are partly to fully degraded by heterotrophic bacteria in the uppermost millimeters of the sediment and so they are thought to be virtually absent deeper in the sedimentary column. Here we present the first evidence of the preservation of EPSs and EPS-mineral aggregates in a 6 m-long sedimentary core obtained from an estuarine point bar in the Gironde Estuary. EPSs were extracted from 18 depth intervals along the core and their physicochemical properties were characterized by (i) wet chemical assays to measure the concentrations of polysaccharides and proteins, and EPS deprotonation of functional groups, (ii) acid-base titrations, and (iii) Fourier transform infrared spectroscopy. EPS-sediment complexes were also imaged using cryo–scanning electron microscopy. The results were compared to sediment properties including facies, grain size, and total organic carbon. Our results showed a predictable decrease in EPS concentrations (proteins and polysaccharides) and reactivity from the surface biofilm to a depth of 0.5 m, possibly linked to heterotrophic degradation. Concentrations remained relatively low down to ca. 4.3 m deep. Surprisingly, at that depth EPSs abundance was comparable to the surface, and showed a downward decrease to 6.08 m. Cryo-SEM showed that the EPS complexes with sediment were abundant at all studied depth. EPS composition did not change substantially from the surface to the bottom of the core. EPS properties showed no statistical correlation with grain size, TOC, or depth. However, maximum EPS concentrations were found at the top of tide-dominated sedimentary sequences, and very low concentrations were found in river flood-dominated sedimentary sequences. Based on this observation, we propose a scenario where biofilm development and EPS production is maximal when (i) the point bar and the intertidal areas were the most extensive, i.e., tide-dominated sequences and (ii) the tide-dominated deposit was succeeded by rapid burial beneath river flood sediments.